Review of the Experience with the Policy Support Instrument. (Policy Papers; Policy Paper ;, 2009)
This review is focused mainly on the implementation of the Policy Support Instrument (PSI) against the goals and expectations set out by the Executive Board. Some possible modifications to the PSI that have been considered by various stakeholders are also touched upon in the concluding section. This review was conducted in parallel with ongoing work on a new architecture of lending facilities for low-income countries (LIC). Based on the results of this review, the reform of LIC facilities is not expected to alter the case for the PSI as a complement to financing instruments.